ANALISIS KONTEN PENERAPAN GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN TAMBANG BARUBARA (Studi Kasus Pada Laporan Tahunan PT Atlas Resources Tbk. Dan PT Golden Energy Mines Tbk. Tahun 2014 dan 2015) - Sinaga, Devy Dame Maria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Good Corporate Governance (GCG) is one of successful keys of companies to grow in today's global competition. The number of cases of fraud occurring due to less transparency and less supervision caused decrease of public reliance on financial statements. Implementation of effective GCG is expected to be able to fulfill the needs of shareholders and stakeholders and to increase their confidence back. This research is a qualitative research with case study approach on content analysis of the annual report from both of mining corporation, namely PT Atlas Resources Tbk and PT Golden Energy Mines Tbk year 2014 and 2015. The purpose of this research was to analyze the extent of the application of the principles of corporate governance practiced by KNKG 2006 in both of mining corporation.The results of this research shows that namely PT Atlas Resources Tbk and PT Golden Energy Mines Tbk has implemented to report the application of the principles of transparency, accountability, independency, responsibility and fairness in their company. The application is good enough. However, there are differences in the application of GCG in both of mining corporation. Every year, each of these companies improved to the application of the principles of GCG to follow the regulations continue to be refined. PT Golden Energy Mines seems to have a stronger commitment and more real consistency on the implementation of GCG practices than PT Atlas Resources Tbk.Keywords: Good Corporate Governance, transparency, accountability, responsibility, independency, fairness.